If 2x = 3y = 12z, prove that x = 2yz/y – z.
Solution:
It is given that
2x = 3y = 12z
Consider
2x = 3y = 12z = k
Here
2x = k where 2 = (k)1/x
3y = k where 3 = (k)1/y
12z = k where 12 = (k)-1/z
We know that
12 = 2 × 2 × 3
Therefore, it is proved.
More Solutions:
- Simplify the following: (i) (81/16)-3/4.
- Simplify the following : (i) (2a-3b2)3
- Simplify the following: (i) 3a/b-1 + 2b/a-1
- Simplify the following: (i) (8/125)-1/3
- Simplify the following : (i) (-1/27)-2/3
- Simplify the following Indices:
- Evaluate the following indices:
- Simplify the following:(i) (3×2)-3 × (x9)2/3
- Simplify the following: (i) (32)0 + 3-4 × 36 + (1/3)-2